2016
DOI: 10.1051/matecconf/20166600060
|View full text |Cite
|
Sign up to set email alerts
|

The Rise Of BIM in Malaysia And Its Impact Towards Quantity Surveying Practices

Abstract: Abstract. Building Information Modeling (BIM) is a new buzzword that is gaining a momentum within the construction industry in Malaysia, and worldwide. BIM is a way of working that involves the automation of the entire project team using a 4D model that can do many of the traditional fuctions of a Quatity Surveyor (QS). As BIM is removing more of the traditional work of QS, there are rising fears that it could threaten the viability of the QS professions especially for small firms that still rely on producing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 4 publications
0
27
0
Order By: Relevance
“…The global construction industry is witnessing a move towards a more collaborative way of working with the growing awareness of, and implementation of, BIM – see Bryde et al (2013), Zainon et al (2016); Ghaffarianhoseini et al (2017), Vass and Gustavsson (2017) and Özorhon and Karaciğan (2020). Team learning, typical of multidisciplinary BIM education, has been seen as a way of achieving competence-based education, especially in vocational studies such as built environment disciplines.…”
Section: Collaborative Multidisciplinary Team Educationmentioning
confidence: 99%
“…The global construction industry is witnessing a move towards a more collaborative way of working with the growing awareness of, and implementation of, BIM – see Bryde et al (2013), Zainon et al (2016); Ghaffarianhoseini et al (2017), Vass and Gustavsson (2017) and Özorhon and Karaciğan (2020). Team learning, typical of multidisciplinary BIM education, has been seen as a way of achieving competence-based education, especially in vocational studies such as built environment disciplines.…”
Section: Collaborative Multidisciplinary Team Educationmentioning
confidence: 99%
“…In the aspect of BIM, adequate digital skills may improve the BIM implementation in construction projects where lack of training and appropriate skills may hinder BIM advancement [14]. The importance of skills in implementing BIM in the construction industry towards performance can also be seen in the study by [41] that discussed the challenges and opportunities gained from using this technology in the Malaysian construction industry. The study found that when the industry players were equipped with the skills and expertise, BIM can give a better job performance in systemizing the project coordination aspect, a more sustainable output, and reducing the time delivery process for preparing BQ, cost estimation, cost update, and tendering process.…”
Section: Digital Skillmentioning
confidence: 99%
“…In addition to that, the result of the research shows that the ICT utilization aspect has a significant relationship with job performance. This explains that improving the aspect of ICT facilities available in the organization can improve job performance among the staff involved [41]. This includes improving the understanding that BIM can save operation costs, strengthen the collaboration between stakeholders, increase the efficiency of works, reduce risk, and the existence of ICT support.…”
Section: Supportedmentioning
confidence: 99%
“…The implementation of BIM technology has emerged as of the application tools to meet the objectives of escalating productivities in a construction project [7]. BIM is known as a process that could accelerate the project design process 70% faster than conventional process [8].…”
Section: Introductionmentioning
confidence: 99%